Gastrointestinal transit of dosage forms - Khosla, Rajiv (1987)
This thesis describes the results from a series of studies designed to evaluate the gastrointestinal transit of oral dosage forms. The transit of placebo pellet and tablet formulations was monitored using the technique of gamma scintigraphy. The formulations were radiolabelled with either technetium-99m or indium-lil. Four parameters, two physiological and two pharmaceutical, were selected for investigation. All the studies were conducted in healthy male volunteers.